Service Quality Influencing Customer Loyalty of Fitness Centers in Phra Nakhon Si Ayutthaya Province - Khattiyasuwan, Sorapol (Rajapark Journal, 2021)
The objectives of this study were to investigate: 1) levels of each service quality and customer loyalty quantity of the fitness centers 2) relationship among quality of fitness center services and customer loyalty of the fitness centers and 3) how overall and each service quality influence customer loyalty of the fitness centers. 122 people participating in 8 fitness centers located in Phra Nakhon Si Ayutthaya Province were selected as the samples using an accidental sampling technique. Questionnaires consisted of a Likert 5-level scale on service quality and customer loyalty with content validity coefficients .67 - 1.00 and reliability coefficients .82 - .95 were used for collecting data. Mean, standard deviation, simple linear correlation, and multiple regression analysis were used for data analysis. The results of the study are the following; The findings revealed that the fitness centers have generally provided 6 services (buildings and the surrounding area, facilities, locker room, exercise equipment, overall staff, and exercise activities with high quality at good-very good levels. Moreover, the customers participating in the fitness centers have reflected their loyalty to the centers at many levels. In terms of the connection among quality of fitness center services together with customer loyalty of the fitness centers, there was a statistically significant relationship at .01 among them. Following the study results, it was found that the hypothesis of overall service quality influencing customer loyalty was significantly supported but only 3 out of 6 services (facilities, overall staff as well as exercise activities) were statistically significant at .05 respectively influencing the customer loyalty.